BENTUK TINDAK TUTUR DIREKIF ANAK USIA DINI DI PAUD TERPADU SULAWESI PERMATA TONDO PALU - Iriyanti, Iriyanti (BAHASANTODEA, 2016)
Based on the background of the research, the research problem is â€œHow is the form of children directive speech act of PAUD Terpadu Sulawesi Permata Bangsa Tondo Palu?. This research aims at describing the use of directive speech act form of children of PAUD Terpadu Sulawesi Permata Bangsa Tondo Palu. The data were obtained from children speech act with teacher and during their learning process either in the classroom or in outside. The method employed was descriptive qualitative. The data collections were recording and observation. The subject was children of TK B and TK A PAUD Terpadu Sulawesi Permata Bangsa Tondo Palu. The technique data analysis was interactive model. The analysis covered four stages, namely: (1) data collection, (2) data reduction, (3) data displaying and (4) verification/drawing conclusion. the research results reveal that children directive speech act form of PAUD Terpadu Sulawesi Permata Bangsa Tondo Palu consists of (1) imperative form, (2) request form, (3) prohibition form, (4) statement form, (5) question form and (6) refusal form.Â